THREE-DIMENSIONAL OBJECT RECONSTRUCTION - Gomez Mora, Miller; Valencia, Leonardo Flores (Revista Vínculos, 2013)
Tridimensional object reconstruction is achieved by obtaining the object’s representation in the computer memory maintaining the volume and shape features. This is known as three-dimensional model. Depending on the mathematical and conceptual formulation, these models can be classified into three types: geometric models, solid models and volumetric models. The development of these models offers a set of tools that allow us to study the properties of objects that one want to represent and display the information contained on these objects. This facilitates the observer to understand and interpret the information as well as to manipulate and simulate the real object on the computer model. This article aims to review the context in which threedimensional objects reconstruction is developed. We want to establish an overview of terminology to exhibit and raise the problems that arise in this area.